KARAKTERISASI DAN KOMPOSISI BIODIESEL DARI MINYAK JARAK PAGAR (jatropha curcas L.) - Rani, Ismarani; Muharam, Salih; Nomosatryo, Nomosatryo (Fakultas Pertanian Universitas Islam 45 (UNISMA) Bekasi, 2011)
Biodiesel was the process of esterification and transesterification of jatropha oil has a yield of 50% of dry jatropha seeds. Physicochemical characteristics of biodieselfrom jatropha curcas L.), among others, specific gravity (0.89 g/L), acid number (0.549 mg KOH/g), iod number (65.79 gI2/100g), and hydroxy numbers entered into theIndonesian Biodiesel Quality Standards, except for viscosity (9,7 cSt). Characteristics of Fourier Transformation Infrared spectra showed that the absence of the intensity of the OH group show has been a process of methylation of castor oil fatty acids. The composition of fatty acid methyl esters of biodiesel was dominated by the acid that has a double chain of oleic and linoleic acid. These compounds were dominated by oleic acid (39.33%), linoleic (27%), palmitic acid (11.14%) and stearic acid (5.11%).